2018
DOI: 10.1556/2060.105.2018.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of one bout of local vibration exercise with blood flow restriction on neuromuscular and hormonal responses

Abstract: This study aimed to investigate the effects of single local vibration (LV) with and without blood flow restriction (BFR) on muscle activity and hormonal responses. A total of 12 physically inactive males were exposed to 10 sets of intermittent LV (35-40 Hz) on unilateral mid-quadriceps in the supine lying position and LV + BFR (inflated to 140 mmHg) sessions in a repeated-measures randomized crossover design, with a 1-week interval separating the sessions. The results indicated that the electromyography values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Most of the studies examining the hormonal responses induced by vibration during training have been conducted on resistance training and have reported conflicting results, such as an elevation of the plasma testosterone [ 9 ], plasma cortisol [ 10 ] or no change [ 11 13 ]. These mixed results might stem from an insufficient exercise stimulus to elicit a change in hormonal response [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies examining the hormonal responses induced by vibration during training have been conducted on resistance training and have reported conflicting results, such as an elevation of the plasma testosterone [ 9 ], plasma cortisol [ 10 ] or no change [ 11 13 ]. These mixed results might stem from an insufficient exercise stimulus to elicit a change in hormonal response [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functions of these hormones have been investigated in various studies, demonstrating an important role in the physiological processes of growth and development, body metabolism, and regeneration (7)(8)(9). Chen et al investigated the effect of vibration training with blood flow restriction on neuromuscular and hormonal responses (10). They reported that BFR exercise largely increased the level of muscle activity and metabolic responses, with no effect on hormonal responses.…”
Section: Introductionmentioning
confidence: 99%